2005
DOI: 10.1080/0034340052000320888
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Cluster While Building a Firm: Entrepreneurs and the Formation of Industrial Clusters

Abstract: Feldman M. P., Francis J. and Bercovitz, J. (2005) Creating a cluster while building a firm: entrepreneurs and the formation of industrial clusters, Regional Studies39, 129-141. The objective of the paper is to provide a theoretical model of cluster development that is informed by an appreciative interpretation of case studies. It argues that entrepreneurs are a critical element in the formation of clusters. Entrepreneurs are important actors in the development of clusters as complex adaptive systems, where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
290
0
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(330 citation statements)
references
References 9 publications
9
290
0
15
Order By: Relevance
“…The crucial factor for this is to first create synergies around a focal point. One possibility is by increasing the number of companies, especially through spin-offs that are regarded as responsible for the first growth of a cluster (ARTHUR, 1994;FELDMAN et al, 2005;KLEPPER, 2007). The number of spinoffs is not strictly a function of the size or number of existing companies.…”
Section: Jena Economic Research Papers 2007-076mentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial factor for this is to first create synergies around a focal point. One possibility is by increasing the number of companies, especially through spin-offs that are regarded as responsible for the first growth of a cluster (ARTHUR, 1994;FELDMAN et al, 2005;KLEPPER, 2007). The number of spinoffs is not strictly a function of the size or number of existing companies.…”
Section: Jena Economic Research Papers 2007-076mentioning
confidence: 99%
“…One of the main factors that turn an emerging cluster into a growing one are pervasive spin-off processes (FELDMAN et al, 2005). Although a gradual transition from an emerging cluster to a functioning and growing cluster is possible, during the growth phase of markets, in which the existing companies are well-positioned, the crucial push often stems from isolated events and sudden changes in exogenous factors like alterations in the leading companies' organisational structures (LONGHI, 1999;FELDMAN, 2001) or a change in the technological framework (DALUM et al, 2005).…”
Section: Jena Economic Research Papers 2007-076mentioning
confidence: 99%
“…In accordance with the economic conceptualisation of entrepreneurship as a 'local event' (Audretsch et al, 2010;Bönte et al, 2009;Feldman, et al 2005;Romanelli and Schoonhaven, 2001;Stam, 2007) the self-employed or entrepreneurs are thought to be strongly 'rooted' in place (Audretsch et al, 2010;Hanson, 2003;2009). The prevailing 'residential rootedness'-hypothesis is based on research focussing on firms and their networks within the region rather than individuals within firms (Armington and Acs 2002;Stuart and Sorenson, 2003; also noted by Hanson and Blake 2009, page 137), and these studies based upon micro data lack comparative research designs (Hanson, 2003;Harrison et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However it has been observed that many of the tools and data available to those engaged in cluster research have known shortcomings particularly related to descriptive data on firm activity and a number of commentators have given the opinion that such deficiencies can lead ultimately to significant errors and omissions related to the discernment of clustering activity (Feldman, Francis and Bercovitz 2005) and particularly by (Porter 1998c) when he complained, in relation to cluster boundaries, that they:…”
Section: "The Popular Term Cluster Is Most Closely Related To This Lomentioning
confidence: 99%